Hubungan antara Perilaku Sanitasi Lingkungan dengan Kejadian Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Tarus - Rusmini Marslan Arsyad; Engelina Nabuasa; Enjelita M. Ndoen (Universitas Nusa Cendana, 2020)
DHF is one of the widespread infectious diseases in Indonesia, with an increased infected number of sufferers. DHF case is closely related to environmental sanitation, wich causes the availability of breeding places for the Aedes aegypti mosquito vectors. The study was to determine the relationship between environmental sanitation behavior and the case of DHF in the working area of the Tarus Community Health Center in 2020. The study design was descriptive-analytical with a cross-sectional study approach. The sample was_99 respondents taken by simple random sampling technique. Data was collected from interviews and analyzed using the Chi-square test. The results showed that the varuabels of knowledge (p = 0.000), attitudes (p = 0.021), and actions to environmental sanitation (p = 0.000) were related to the DHF case. The Tarus Community Health Center should increase outreach activities and family empowerment efforts related to the prevention and control of DHF.